Improvement of organizational and economic mechanisms of pilgrimage tourism development in Kashkadarya region - Uzokov Norboyevich, Jamshid (THE INNOVATION ECONOMY, 2024)
This article presents the organizational and economic mechanisms for the development of pilgrimage tourism. The number, location and location of cultural heritage sites in the districts of the Kashkadarya region are indicated. The organizational and economic mechanisms for the development of pilgrimage tourism in the regions are comprehensively analyzed on a scientific basis and proposals and recommendations are given. Based on the great potential of the Republic of Uzbekistan in the direction of pilgrimage tourism, the wide involvement of fraternal nations and peoples in the cultural heritage existing in the territories of the country, increasing the love of the younger generation for the history and nationalcultural heritage of our peoples, cooperation in the field of tourism with member states of the Organization of Turkic states The scientific article reflects that it is aimed at further expanding ties, jointly promoting national cultural heritage to the world, diversifying tourism products and services aimed at various market segments, increasing their competitiveness, and creating a favorable environment for domestic and international pilgrimage tourism. At the moment, work to improve the organizational and economic mechanisms for the development of pilgrimage tourism requires scientific research with a serious approach to the issue. These issues are described in the article